Kinetic studies on an algal biofilm reactor for raw sewage water treatment - Gera, Gayatri S.; Yewalkar, Swati N.; Nene, Sanjay; Kulkarni, Bhaskar D.; Kamble, Sanjay P. (Chemical Engineering & Technology, 2016)
A packed-bed algae biofilm reactor was developed using porous and nonporous dual packings. The biofilm was cultivated on reticulated polyurethane foam cubes. The nonporous glass Raschig rings were taken as bed support that helps to remove generated gas from the system. The effect of variables such as column length-to-diameter ratio, catalyst cube dimension, and feed flow rate on the treatment of sewage water was studied. The reaction kinetics indicates that the nutrients uptake rate is dependent on both pore and film diffusion. The kinetics of uptake of nutrients follows a pseudo first-order reaction. From the pseudo reaction rate constant, Thiele modulus and effectiveness factor were calculated and a kinetic model equation for fractional nutrient uptake was developed in terms of operating variables. The model can predict the reaction rate with low deviation. The results obtained may be valuable for large-scale treatment of sewage water.